Economic projections and rules-of-thumb for monetary policy - Athanasios Orphanides; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
Monetary policy analysts often rely on rules-of-thumb, such as the Taylor rule, to describe historical monetary policy decisions and to compare current policy to historical norms. Analysis along these lines also permits evaluation of episodes where policy may have deviated from a simple rule and examination of the reasons behind such deviations. One interesting question is whether such rules-of-thumb should draw on policymakers' forecasts of key variables such as inflation and unemployment or on observed outcomes. Importantly, deviations of the policy from the prescriptions of a Taylor rule that relies on outcomes may be due to systematic responses to information captured in policymakers' own projections. We investigate this proposition in the context of FOMC policy decisions over the past 20 years using publicly available FOMC projections from the biannual monetary policy reports to the Congress (Humphrey-Hawkins reports). Our results indicate that FOMC decisions can indeed be predominantly explained in terms of the FOMC's own projections rather than observed outcomes. Thus, a forecast-based rule-of-thumb better characterizes FOMC decision-making. We also confirm that many of the apparent deviations of the federal funds rate from an outcome-based Taylor-style rule may be considered systematic responses to information contained in FOMC projections.
urn:nbn:de:hebis:30-56898
Keywords: E52; 330; Monetary Policy; Forecasts; FOMC; Policy Rules; Geldpolitik; Taylor-Regel; Wirtschaftsprognose; Zentralbank; USA